The Role of Bauman Moscow State Technical University in Scientific and Methodical Support of Higher School of Russia (To the 30th Anniversary of Educational and Methodical Association) - S. V. Korshunov (Высшее образование в России)
The paper analyzes the contribution of scientists, teachers, engineers of Bauman Moscow State Technical University (the former Moscow Craft School, then Moscow Higher Technical School, Imperial Moscow Technical School) to the development of scientific and methodical provision of Russia’s higher school and world engineering education. The author emphasizes the value of the “Russian method of training in crafts”. The characteristics of level system of engineering education in the 19th and 20th century are given such as: combination of theoretical, general engineering disciplines and practical specialized preparation; polytechnicalization of engineering education in Russia; compatibility of level education in baccalaureate and in magistracy with training according to specialties; inclusion of economic training in engineering education; the need of comprehensive continuous modernization of engineering education in accordance with the changing requirements of employers to university graduates. The paper highlights such aspects of MSTU activities as: detachment from Moscow Higher Technical School a number of engineering institutes in the 1930th years; optimization of training terms in engineering specialties; convergence of technical and classical university education, universitization of engineering education, creation of the Association of technical universities, the activities of the scientific and educational centers, which can be viewed as a new stage of the Russian method of engineers’ training, the contribution of Bauman Moscow State Technical University to the development of information technology in engineering education, BMSTU’s participation of in state and public governing of higher education system; the deepening of the international academic mobility.